Serovars of Salmonella spp isolated from broiler chickens and commercial breeders in diverse regions in Brazil from July 1997 to December 2004 - Kanashiro,AMI (2005)
Avian salmonellosis is a worldwide problem to the poultry industry, from the point of view of animal health and public health as well. The aim of the present study was to survey the most common Salmonella serovars in commercial breeders or broiler flocks from several regions in Brazil. The results of the present study indicated a high incidence of S enterica subspecies enterica serovar Enteritidis in breeders (57.5%) and broilers flocks (84.0%). The importance of these findings lies in the fact that S. Enteritidis has become the most frequent serovar responsible for foodborne outbreaks and sporadic cases of salmonellosis in humans.